2019
DOI: 10.1007/s00415-019-09209-z
|View full text |Cite
|
Sign up to set email alerts
|

The histopathological spectrum of malignant hyperthermia and rhabdomyolysis due to RYR1 mutations

Abstract: ObjectiveThe histopathological features of malignant hyperthermia (MH) and non-anaesthetic (mostly exertional) rhabdomyolysis (RM) due to RYR1 mutations have only been reported in a few cases.MethodsWe performed a retrospective multi-centre cohort study focussing on the histopathological features of patients with MH or RM due to RYR1 mutations (1987–2017). All muscle biopsies were reviewed by a neuromuscular pathologist. Additional morphometric and electron microscopic analysis were performed where possible.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 58 publications
(66 reference statements)
0
28
0
1
Order By: Relevance
“…Indeed, type X glycogenosis was reported in patients whose muscle biopsy showed tubular aggregates (Naini et al, 2009; Vissing et al, 1999). Identification of mutations in RYR1 represents an unexpected finding, since myopathies caused by RYR1 mutations are usually associated with the presence of cores of different morphologies in muscle biopsy of these patients (Knuiman et al, 2019; Lawal et al, 2020). Indeed, despite in the last years the list of RYR1 ‐related myopathies has been further expanded with the inclusion of novel histological findings such as dusty cores (Garibaldi et al, 2019) and protein aggregate inclusions (Machnicki et al, 2021), RYR1 mutations have never been identified in patients with TAM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, type X glycogenosis was reported in patients whose muscle biopsy showed tubular aggregates (Naini et al, 2009; Vissing et al, 1999). Identification of mutations in RYR1 represents an unexpected finding, since myopathies caused by RYR1 mutations are usually associated with the presence of cores of different morphologies in muscle biopsy of these patients (Knuiman et al, 2019; Lawal et al, 2020). Indeed, despite in the last years the list of RYR1 ‐related myopathies has been further expanded with the inclusion of novel histological findings such as dusty cores (Garibaldi et al, 2019) and protein aggregate inclusions (Machnicki et al, 2021), RYR1 mutations have never been identified in patients with TAM.…”
Section: Discussionmentioning
confidence: 99%
“…RYR1 ‐related myopathies are generally non‐progressive or slowly progressive and are characterized by a wide range of symptoms including mild muscle weakness, hypotonia, motor developmental delay, orthopaedic complications, including scoliosis and foot deformities, and, more rarely, to cases with wheelchair dependence and respiratory failure (Dowling et al, 2014; Jungbluth et al, 2018; Lawal et al, 2020). More recently, RYR1 variants have also been associated with other atypical phenotypes including exercise‐induced rhabdomyolysis (Knuiman et al, 2019), some forms of periodic paralysis (Jungbluth & Hanna, 2018), adult‐onset distal myopathy (Machnicki et al, 2021; Pietrini et al, 2004; Zhou et al, 2010), mild calf‐predominant myopathy (Jokela et al, 2019), foetal akinesia deformation sequence syndrome/arthrogryposis multiplex congenital and lethal multiple pterygium syndrome (Alkhunaizi et al, 2019 ) .…”
Section: Introductionmentioning
confidence: 99%
“…RYR1 -related myopathies are classified in different subtypes mostly based on the histopathological features observed in muscle biopsies of patients ( Abath Neto et al, 2017 ; Garibaldi et al, 2019 ; Knuiman et al, 2019 ; Lawal et al, 2020 ; Table 1 ). Nevertheless, it must be considered that the histological phenotype associated with RYR1 mutations can differ in individuals with the same variant or change with age in the same patient, and thus classification of RYR1 -related myopathies merely based on the histopathological pattern is more complicated than expected.…”
Section: Ryr1 -Related Myopathiesmentioning
confidence: 99%
“…MH appears to have a higher prevalence in males than females, likely because of smaller muscle mass and a protective effect of estrogens in the latter ( Michelucci et al, 2017b ). Although ∼10% of patients present with no alteration at histological analysis, the remaining 90% show a variable range of alterations, including an increase in fiber size variability, internal nuclei, type 1 fiber predominance, and loss of oxidative stain that is rarely associated with the presence of cores and rods ( Knuiman et al, 2019 ). These histological alterations, although variable, may represent mild features that, in RYR1 -related myopathies, evolve to more severe histological and structural alterations.…”
Section: Ryr1 -Related Myopathiesmentioning
confidence: 99%
“…Muscle imaging is usually normal, while muscle biopsy may show variable findings, ranging from normal or non-specific mild myopathic changes to cores, minicores, internalized nuclei and type 1 muscle fiber predominance, more typical to a congenital myopathy. Dantrolene has been proposed as a potentially preventing agent for episodes of rhabdomyolysis [51,[81][82][83][84][85][86][87].…”
Section: Ryr1-related Myopathiesmentioning
confidence: 99%